Analisis Tingkat Pengetahuan, Lokasi dan Literasi Keuangan Syariah terhadap Minat Masyarakat Menggunakan Produk Bank Syariah Indonesia Cabang Kabupaten Belitung - Damayanthy, Dessy; Norman, Efrita; Ramadhanti, Desy Kurnia (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Sharia banking is an implementation of a larger sharia economic system. This research aims to find out whether the level of knowledge, location and sharia financial literacy influence people's decisions to use Bank Syariah Indonesia products at the Belitung Regency branch. This research uses a descriptive quantitative approach. The techniques used in sampling are non-probability sampling and convenience sampling and the data analysis technique used is multiple linear regression. The results of the analysis using the t test illustrate that the level of knowledge influences people's interest with a t value of 4.461 which is greater than t table 1.991. Location has no influence on people's interest in using Bank Syariah Indonesia products based on a tcount value of 6.797 which is greater than ttable 1.991. Meanwhile, sharia financial literacy influences people's interest in using Bank Syariah Indonesia products with a tcount value of 6.797 which is greater than ttable 1.991. Furthermore, based on multiple linear regression testing, the coefficient of determination R2 is 0.641 or 64.1%, which means that the variables of level of knowledge, location and sharia financial literacy influence 64.1% of people's interest in using Bank Syariah Indonesia products and the remaining 35.9% is explained by other variables outside the variables studied in the research such as government policy and public demand.